KARUNGUT MUSIC REDUCES ANXIETY OF ADOLESCENT PREGNANT MOTHER - Riyanti Riyanti; Legawati Legawati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Adolescent pregnancy is being a problem in Indonesia. Adolescent pregnancy can bring problem not only to the baby’s health but also the mother’s health as well. It can cause problem in society too. The pressure from family and society towards adolescent who got pregnant, especially if they get pregnant without marriage can lead the mother to face anxiety during the pregnancy. The anxiety during pregnancy can bring negative impact to the baby and mother. This study aims to determine the effect of Karungut music to the anxiety level among pregnant adolescent in Kapuas Regency, Indonesia. Methods: This study was an analytical study with a quasi-experimental. Totally 60 respondents were recruited in this study used simple random sampling. 30 respondents were chosen to be experimental group meanwhile the rest as control group. The data was analyzed in univariate and bivariate analysis. binary logistic regression was used to analyze in multivariate level. Results: Majority of the respondents in this study were did the Antenatal Care regularly (55%), had high motivation for pregnant (51.7%), got families support (71.7%) but not from the health workers (83.3%). The multivariate analysis showed that heard Karungut music can reduce the anxiety level among pregnant adolescent (OR= 3.33) after controlling other variables. Conclusion: Listening Karungut music during pregnancy can reduce the anxiety among pregnant woman. It can be considered as an alternative way to improve the health status among pregnant adolescent by reducing one of risk factor that can affect to the pregnancy. Supporting from family and health workers also important during pregnancy to reduce the anxiety.